Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.12659/msm.924544
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sirtuin-1 in Neonatal Hypoxic-Ischemic Encephalopathy and Its Underlying Mechanism

Abstract: Background Neonatal hypoxic-ischemic encephalopathy (HIE) is a dreaded disease and one of the leading causes of severe neurological dysfunction in neonates. The present study explored the functions of Sirtuin-1 (SIRT1) in neonatal HIE. Material/Methods A HIE neonatal rat model was generated to determine SIRT1 levels in brain tissues. Cell apoptosis and cell viability were analyzed by flow cytometry and MTT assay. qRT-PCR and Western blot analysis were used to assess gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Using molecular docking simulations and cell-based studies, we herein demonstrated that both 4-dmH and heliomycin targeted SIRT1 and inhibited its activity and expression, to attenuate the growth of oral cancer cells. Given that SIRT1 contributes to a complex regulatory network, it is of primary importance to understand the fundamental regulatory mechanisms of SIRT1 in cell death regulation ( Wang et al, 2023 ; Wang et al, 2021a ; Lee et al, 2018 ; Zhu et al, 2020 ; Ran et al, 2023 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using molecular docking simulations and cell-based studies, we herein demonstrated that both 4-dmH and heliomycin targeted SIRT1 and inhibited its activity and expression, to attenuate the growth of oral cancer cells. Given that SIRT1 contributes to a complex regulatory network, it is of primary importance to understand the fundamental regulatory mechanisms of SIRT1 in cell death regulation ( Wang et al, 2023 ; Wang et al, 2021a ; Lee et al, 2018 ; Zhu et al, 2020 ; Ran et al, 2023 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…NSE, a glycolytic enolase enzyme, is present in the cytoplasm of cells with neuroendocrine differentiation and neurones in the brain. NSE levels can be indirectly estimated to determine the degree of neuronal damage and prognosis of neonatal HIE 26–28 . S100B—an acidic calcium‐binding protein in nervous tissues—is a potential biomarker to determine and evaluate minor brain damage of neonatal HIE 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…NSE levels can be indirectly estimated to determine the degree of neuronal damage and prognosis of neonatal HIE. 26 , 27 , 28 S100B—an acidic calcium‐binding protein in nervous tissues—is a potential biomarker to determine and evaluate minor brain damage of neonatal HIE. 28 , 29 Our results showed that the levels of brain injury‐related biomarkers, namely NSE and S100B, were increased in the brain tissue of neonatal HIE rats, indicating that HIE induced brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Using molecular docking simulations and cell-based studies, we herein demonstrated that both 4-dmH and heliomycin targeted SIRT1 and inhibited its activity and expression, to attenuate the growth of oral cancer cells. Given that SIRT1 contributes to a complex regulatory network, it is of primary importance to understand the fundamental regulatory mechanisms of SIRT1 in cell death regulation [57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%